The Use of Props Educative For Enhancement Teacher creativity _ Towards Quality PAUD through Teacher Training - Dian Puspita; Lilis Suryani; Rahmi Utami; Dewie Hartati; Neneng Yuliana; Luluk Maryam (International Conferences on Early Childhood Education Proceedings, 2023)
This research was motivated by the lack of teacher creativity in making APE , as well as the limited knowledge of East Cikarang IGRA teachers about Educational Aids (APE). APE as a learning medium is generally a separate obstacle for an institution, especially teachers. The obstacle in this case is related to the availability and very limited variety of APE in institutions. As well as the limited ability of teachers to do design and creativity. Therefore, training on making APE, namely smart trees, was held to increase teacher creativity in teaching IGRA teachers in East Cikarang District, Bekasi Regency, which was held at RA Senyum Muslim. This study aims to find out whether the use of educational aids can increase teacher creativity in the framework of leading to quality PAUD. This training is carried out for one full day, namely from 08.00 WIB to 16.00 WIB, on March 11, 2023. The method used in this research is qualitative approach with descriptive method. This study further concludes that the use of educational aids can increase teacher creativity in the framework of leading to quality PAUD.